The Dynamics of Phytoplankton Abundance in the PLTA Koto Panjang Reservoir inBatu Bersurat Village, XIII Koto KamparDistricts, Kampar Regency, Riau Province - Ester Romastika Turnip; Tengku Dahril; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTPhytoplankton will respond to the nutrient material that is input into the Koto Panjang Reservoir in Batu Bersurat. The dynamics of phytoplankton abundance will occur depending on nutrients and light intensity based on time and depth. This study aims to look at the dynamics of phytoplankton abundance based on time and depth. This research was conducted in June-July 2019. The sampling locations were determined by 3 stations 4 times with a time interval of 1 week. At each station, there are 3 sampling points, namely on the surface, at 2 Secchi depth and at 4 Secchi depth. The parameters measured are temperature, brightness, depth, pH, DO, CO2, nitrate, and phosphate. Based on measurements at different depths, it was found that the abundance of phytoplankton was most surface and decreased at depths of 2 Secchi and 4 Secchi. Based on time, phytoplankton abundance is increasing every week. Water quality parameters recorded as follows, temperature 29-31 oC, transparency 153.5-161.25 cm, pH 5, DO 6.2-6.8 mg/L, CO2 7.3-9.3 mg/L, nitrate 0.056-0.082 mg/L and phosphate 0.59-0.96 mg/L.Keyword: The Dynamic of Phytoplankton, Water Quality Parameters, Reservoir Puddles